Adenoid Cystic Carcinoma of the Trachea Resulting in Fatal Asphyxia. Issue 1 (16th November 2016) - Huston, Butch; Froloff, Victor; Mills, Kelly; McGee, Michael
Abstract: Primary malignant tumors of the trachea are uncommon. The authors report a case of a 72‐year‐old female who died from asphyxia due to an undiagnosed obstructing adenoid cystic carcinoma of the trachea. The decedent became unresponsive while eating cereal and was pronounced upon arrival at the local hospital. The autopsy revealed a near occlusive tumor mass just superior to the bifurcation of the distal trachea. There was no evidence of aspiration. The death was the result of asphyxia due to obstruction of the trachea by an adenoid cystic carcinoma. This case demonstrates that an obstructive tumor mass may remain undiagnosed until an obstructive episode results in a sudden death.